AB0310 Prognostic Factor for Forefoot Deformity in Early Rheumatoid Arthritis. (9th June 2015) - Hara, R.; Tanaka, Y.; Fujimoto, T.; Akai, Y.; Kobata, Y.; Kido, A.; Shimmyo, N.; Fujimura, T.
Abstract : Background: Disease activity score (DAS) 28 and simplified disease activity index (SDAI) and clinical disease activity index (CDAI) are often used for clinical assessment, and these criteria dose not include assessment of joints in the feet. Residual synovitis of the MTP joints and various factors such as inflammatory marker, drugs and weght-bearing possibly cause various deformities of the forefoot and lead to functional, cosmetic problems. Objectives: To determine prognostic factors of forefoot deformity in early rheumatoid arthritis (RA). Methods: Twenty-four outpatients with RA before tight control were enrolled. At baseline, the mean age of patients was 57.8 years and the mean disease duration was 11.2 months. The mean body mass index (BMI) was 22.0 kg/m 2 . The mean DAS28, SDAI and modified health assessment questionnaire (mHAQ) at baseline was 4.84, 21.9 and 0.29. The mean CRP and MMP-3 was 1.7 mg/dl and 153 ng/ml. Eleven patients (46%) were treated with conventional synthetic disease modified anti-rheumatic drugs (csDMARDs) and 8 patients (33%) were treated with glucocorticoids (GCs, mean dose of prednisolone 5.6mg). Nine patients (38%) were treated biological agents at final follow up. As ultrasonographic assessment, bilateral first IP joint, the second to fifth PIP joint, the first to fifth MCP and MTP joints were assessed by semi-quantitative assessment (0 - 3) using power Doppler ultrasonography (PDUS). The sum score of all joints and MTP joints was used as total PDUS (TPD) and foot PDUS (FPD). Radiographic damages of feet were evaluated by using van der Heijde modified total sharp score (footTSS, 0 - 168). Radiographic forefoot deformities were evaluated by using hallux valgus angle (HV), 1st to 2nd metatarsal angle (M1M2) and 1st to 5th metatarsal angle (M1M5). Both radiographic assessment were performed at baseline and final follow up (mean 2.7 years), and the sum of these angle (HV + M1M2 + M1M5) was used as total deformity score (TDS). Results: Twenty-one (87.5%) and 18 (75%) patients achieved DAS28 and SDAI remission after tight control. At final follow up, all deformity angle were significantly progressed and mean ΔHV, ΔM1M2, ΔM1M5 and ΔTDS was 3.58, 2.29, 3.88 and 9.75 respectively. ΔTDS were not correlated with ΔfootTSS (ρ=0.09, p=0.68). DAS28, SDAI, TPD, FPD, CRP, MMP-3 and BMI were not correlated with ΔTDS, whereas univariate linear analysis identified significant correlation with GCs and ΔTDS (p=0.009), and multiple regression analysis revealed GCs was a independent risk for forefoot deformity (p=0.01). Conclusions: Forefoot deformity in RA progressed even if clinical remission was achieved. Baseline prognostic factor for forefoot deformity in early RA was oral low dose GCs in the early stage of treatment. Disclosure of Interest: None declared